2007
DOI: 10.1099/vir.0.82772-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural studies of the vaccinia virus virulence factor N1 reveal a Bcl-2-like anti-apoptotic protein

Abstract: Vaccinia virus (VACV) encodes many immunomodulatory proteins, including inhibitors of apoptosis and modulators of innate immune signalling. VACV protein N1 is an intracellular homodimer that contributes to virus virulence and was reported to inhibit nuclear factor (NF)-κB signalling. However, analysis of NF-κB signalling in cells infected with recombinant viruses with or without the N1L gene showed no difference in NF-κB-dependent gene expression. Given that N1 promotes virus virulence, other possible function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
222
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(230 citation statements)
references
References 49 publications
5
222
3
Order By: Relevance
“…23,24 N1L also exists as a dimer, 14 but no domain swapping occurs in that case. 12,13 Other structural studies of Bcl-2 family proteins suggest that the fold is largely unaffected by the presence or absence of the C-terminal membrane anchor. If the C-terminal segments, absent in our construct, are taken into consideration, the dimer structure we describe is compatible with membrane anchoring (see, for example, Figure 1b, and note the dyadrelated a7 segments projecting towards the viewer).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…23,24 N1L also exists as a dimer, 14 but no domain swapping occurs in that case. 12,13 Other structural studies of Bcl-2 family proteins suggest that the fold is largely unaffected by the presence or absence of the C-terminal membrane anchor. If the C-terminal segments, absent in our construct, are taken into consideration, the dimer structure we describe is compatible with membrane anchoring (see, for example, Figure 1b, and note the dyadrelated a7 segments projecting towards the viewer).…”
Section: Discussionmentioning
confidence: 99%
“…14 N1L reportedly binds BH3 peptides of Bim, Bak and Bid, 12 and interacts with Bad, Bax and Bid in cells transfected with the N1L gene. 13 In contrast, virus lacking F1L (VVDF1L) results in apoptosis of infected cells in culture, 10,15 suggesting that Figure 5 Novel consensus sequence motif redefining the BH4 domain. The novel BH4 motif is formed by f 1 f 2 X X f 3 f 4 , where X is any amino acid, f is a hydrophobic residue and f 3 is an aromatic residue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Structural studies of M11L (37,38) revealed that although it lacks sequence similar-ity to the Bcl-2 family of proteins it adopts a Bcl-2-like fold and engages BH3 ligands utilizing the canonical BH3 domain binding groove (38). Vaccinia virus N1L was shown to also adopt a Bcl-2-like fold (39,40), which enabled it to assume dual functionality by mediating intrinsic apoptosis via the canonical Bcl-2 binding groove as well as NF-B signaling via an additional non-canonical site (41). Similarly, deerpox virus DPV022 was shown to be a Bcl-2-like protein, albeit with a dimeric topology due to a domain swap (42).…”
mentioning
confidence: 99%